THE SYMBOLIC MEANING OF SEURUMBEK RECITATION IN THE KEUNDURI BLANG TRADITION: STUDY OF LIVING QUR'AN IN PIDIE, ACEH, INDONESIA - Bahri, Samsul; Simangunsong, Ali Abdurahman; Abraar, Muhammad Nuzul; Shaleh, Abdul Rahman (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2024)
The seurumbek, a mushaf manuscript by Tgk. Chik Dipasi, is highly revered and considered sacred by the community of Waido. The presence and recitation of seurumbek hold great significance in the keunduri blang tradition in Waido, setting it apart from other regions in Aceh. This research aims to explore the description of the implementation of seurumbek recitation and delve deeper into the symbolic meanings created within this tradition. The study employs a qualitative approach as part of field research, utilizing observation, interviews, and direct documentation techniques presented descriptively. The research is conducted in Waido, Pidie Regency, Aceh. The findings reveal that the seurumbek recitation occupies a central position in the keunduri blang tradition, evident from the special treatment it receives, both in storage and during the recitation process. Seurumbek recitation also creates complex symbols reflecting the relationship between humans and God, ancestors, others, and oneself. This practice serves as a mediator to draw closer to Allah, with symbolic actions such as shading, kissing, and showing respect for seurumbek reflecting reverence for Tgk. Chik Dipasi. Seurumbek recitation also symbolizes social relationships by strengthening Islamic brotherhood in the community. Additionally, it brings tranquility, patience, and sincerity as symbols of an individual's relationship with oneself.